Soil chemical attributes and nutrition state of Cabernet Sauvignon (Vitis vinifera L.) grapevine Santa Catarina high lands - Mafra, Maria Sueli Heberle; Cassol, Paulo Cezar; Miquelluti, David José; Ernani, Paulo Roberto; Gatiboni, Luciano Colpo; Ferreira, Evandro Zacca; Barros, Marlon de; Zalamena, Jovani; Grohskopf, Marco André (Revista de Ciências Agroveterinárias, 2011)
The objective of this work was to evaluate the grapevine nutrition and its relation with some soil chemical attributes. The study was carried out in São Joaquim, SC, Southern of Brazil, in a commercial vineyards using Cabernet Sauvignon cv. grafted on Paulsen 1103 rootstock. Soil and plant tissue samples were collected in 21 plots of 240 m2 each, containing four sub plots. The soil chemical attributes evaluated were pH, total acidity (H+Al), organic mater, total N, extractable P and K, and exchangeable Ca, Mg and Al. In tissue were evaluated N, P, K, Ca and Mg. There were differences among blots with regard to soil chemical attributes and the contents of nutrient in both leaves and petioles. The soil presented very high values for organic mater, extractable K and exchangeable Ca and Mg. The contents of N in the petioles and the Ca in both leaves and petioles were below to the intermediate range, according Comissão de Química e Fertilidade do Solo do Rio Grande do Sul e Santa Catarina. The contents of K and the K/Mg ratio in leaves and petioles were above the sufficiency range. There was association between the soil nutrients availability and their contents in the leaves, especially a negatives linear correlation between soil exchangeable K and contents of Mg in the leaves and between soil exchangeable Mg and K in the leaves, confirming the antagonic relationships between these two nutrients in the plant uptake. The soil pH was positively correlated with N contents in petiole. The concentration of K, Ca and Mg in the leaves was better correlated with their saturations in the CEC than with their contents in the soil.